Stakeholder Profiles and the Status of Alternative Learning System Implementation in the Selected Community Learning Centers - Arlene S. Rillorta; Priscila A. Santos (Future Science / FSH-PH Publications, 2026)
This study examined the profiles of Alternative Learning System (ALS) teachers and students, selected Community Learning Centers (CLCs), and the status of the implementation of the Alternative Learning System (ALS) in four CLCs. The research included 32 ALS learners and four ALS teachers. The researchers utilized structured questionnaires, a resource checklist and purposive sampling in gathering information. Average ratings, frequencies, and percentages were used to summarize the data. The learner profiles were dominated by students from low-income homes, men, adolescents, and jobless individuals. Financial hardships and family obligations were the most common reasons given for quitting formal education. The four married women who taught ALS ranged in age from 42 to 63. Two have master's degrees and two have bachelor's degrees, and all have specific training in special needs schooling. The four CLCs offered secure classrooms, facilities for learning activities, and permanent learning spaces; they were categorized as Type 3 centers. Important educational resources were still scarce, tho. The chosen centers lacked or had insufficient furniture, digital resources, instructional aids, visual aids, internet access, and supplemental materials. Despite these drawbacks, teachers and students reported generally positive experiences with ALS education. Positive scores were given to teacher assistance, course relevance, instructional tactics, and engagement; poorer ratings were given to the sufficiency of learning resources. The results indicate a disparity between the availability of basic facilities and the scarcity of digital and instructional resources that support them.